Rancang Bangun Alat Sortir Buah Apel Berdasarkan Perbedaan Ukuran dan Warna Menggunakan Mikrokontroller Arduino - M. Noor Khafit; Nur Khamdi; Jajang Jaenudin; Edilla Edilla (JTEV (Jurnal Teknik Elektro dan Vokasional), 2023)
Indonesia is a country rich in natural resources, especially in agriculture. Plantation products, both in the form of raw materials and processed products, are one of the major contributors to the country's foreign exchange. Local apples from Batu City are one of the products exported. However, the process of sorting apples still uses human labor and is an obstacle for Indonesia to increasing the economic value of local apples in the export market. Therefore, an automatic sorting system was created to separate apples based on size and color. The system uses experimental methods and collects empirical data from each process for more accurate automated sorting. The size sorting mechanic consists of a conveyor that is designed to be tilted at 30 degrees to facilitate the process of sorting apples and then measuring rollers, hoopers, and shelters. The data processing controller used is Arduino Mega 2560. The main data input comes from the TCS3200 color sensor and proximity sensor. Meanwhile, the sorting executor uses 1 MG996 servo motor and 2 MG90s servo motors. Although there are constraints on the TCS3200 sensor which are sensitive to distance and light which affect the RGB value results, this automatic sorting system can successfully sort apples with a success rate of 96% for size sorting and 80% for color sorting.